Expression of TopBP1 in hereditary breast cancer - Forma, Ewa (Springer Netherlands, 2012)
TopBP1 protein displays structural as well as functional similarities to BRCA1 and is involved in DNA replication, DNA damage checkpoint response and transcriptional regulation. Aberrant expression of TopBP1 may lead to genomic instability and can have pathological consequences. In this study we aimed to investigate expression of TopBP1 gene at mRNA and protein level in hereditary breast cancer. Real-time quantitative PCR was performed in 127 breast cancer samples. Expression of TopBP1 mRNA in lobular carcinoma was significantly lower compared with ductal carcinoma (p < 0.05). The level of TopBP1 mRNA appeared to be lower in poorly differentiated (III grade) hereditary breast cancer in comparison with moderately (II grade) and well-differentiated cancer (I grade) (p < 0.05 and p < 0.001 respectively). We analyzed TopBP1 protein expression using immunohistochemistry and Western blot techniques. Expression of TopBP1 protein was found to be significantly increased in poorly differentiated breast cancer (III grade) (p < 0.05). The percentage of samples with cytoplasmic apart from nuclear staining increased with increasing histological grade. There was no significant association between level and intracellular localization of TopBP1 protein in hereditary breast cancer and other clinicopathological parameters such as estrogen and progesterone receptors status, appearance of metastasis in the axillary lymph nodes and type of cancer. Our data suggest that decreased level of TopBP1 mRNA and increased level of TopBP1 protein might be associated with progression of hereditary breast cancer.